A family clinic—optimising care for HIV infected children and their families. Issue 6 (1st December 1997) - Gibb, Diana M; Masters, Janet; Shingadia, Delane; Trickett, Sue; Klein, Nigel; Duggan, Candy; Novelli, Vas; Mercey, Danielle
Abstract : A family clinic providing specialist paediatric and adult medical, testing, counselling, and terminal care services for families living with HIV was set up at a paediatric tertiary care hospital in London in 1991. During the first five years, until April 1996, 185 children from 149 families attended, including 119 infected children, of whom 32 have died. Only 5% of mothers were born in the UK; the rest were born in 24 different countries, the majority in sub-Saharan Africa. Less than a quarter of children were cared for by both parents, 61% by mothers alone, and 11% by guardians or foster parents. Of the adult attendees, 76% were women, and more than half were untested when they first attended the clinic. Provision of a family planning service within the family clinic was initiated as a result of women presenting with unplanned pregnancies. Shared care with local clinics is increasing, but with the complexity around the management of paediatric HIV infection, particularly with regard to antiretroviral treatments, there is need for continued specialist input. Coordination among specialist and locally based family services is required to provide flexible, accessible, and up to date care for families living with HIV infection in London.